Injury of the Thalamocingulate Tract in the Papez Circuit in Patients with Mild Traumatic Brain Injury. (March 2016) - Yang, Dong Seok; Kwon, Hyeok Gyu; Jang, Sung Ho
Abstract : ABSTRACT: The thalamocingulate tract between the anterior thalamic nuclei and the cingulate gyrus is a part of the Papez circuit. Using diffusion tensor tractography, injury of the thalamocingulate tract was investigated in patients with mild traumatic brain injury. Two patients (patient 1: a 58-yr-old woman and patient 2: a 49-yr-old man) with head trauma resulting from a car accident were enrolled. They were classified as mild traumatic brain injury and no specific lesion was observed on brain magnetic resonance imaging. These patients complained of memory impairment after head trauma. The entire Papez circuits, including thalamocingulate tract, fornix, mammillothalamic tract, and cingulum, were reconstructed in both hemispheres except for the left thalamocingulate tract: patient 1, it was thinner and discontinued compared with the right thalamocingulate tract; and patient 2, it was not reconstructed. The injury of the left thalamocingulate tract appeared to be related to the memory impairment in these patients. Abstract : Supplemental digital content is available in the text.